SPRACHKONTAKTE DES PORTUGIESISCHEN IM SPÄTMITTELALTER UND IHRE AUSWIRKUNGEN AUF DAS ANREDESYSTEM - Aurelia MERLAN (Studia Universitatis Babeş-Bolyai. Philologia, 2020)
Language Contact of Portuguese During the Late Middle Ages and Its Effect on the Portuguese System of Address Forms. Towards the end of the Middle Ages, various noun phrases for reverential address (like Vossa Mercê) appear in Portuguese and enter into competition with the pronoun vos, finally leading to a restructuring of the system of address forms. Regarding these noun phrases, the present article tries to determine to which degree their appearance may be explained by linguistic contact between Portuguese and Spanish/Italian. For that purpose, the article describes, in the first part, the nature and intensity of these contacts. The second part analyses the reverential noun phrases in three 15th century chronicles which contain (some of) the oldest documented cases of this new strategy of address.